EU-U.S. Terminology and Taxonomy for Artificial Intelligence (2023)
Following the AI Roadmap suggestions for concrete activities aimed at aligning EU and U.S. risk-based approaches, a group of experts engaged to prepare an initial draft AI terminologies and taxonomies. A total number of 65 terms were identified with reference to key documents from the EU and the U.S.
Keywords: /unread